Capturing innovations in grassland-based dairy farms in Sardinia (Italy) - Porqueddu C.; Melis R.A.M.; Sanna F.; Franca A. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Inno4Grass is the acronym for “Shared Innovation Space for Sustainable Productivity of Grasslands in Europe”, an international and multi-actor project gathering prominent farmers’ organizations, extension services, education and research institutions from eight EU countries. The overall objective of the project is to bridge the gap between practice and science communities to ensure the implementation of grassland innovations at farm level. After a brief introduction about the overall structure of Inno4Grass, we will focus on the outcome of a farm survey carried out in Sardinia (Italy). Ten innovative dairy farmers were interviewed. Information was collected using a standardised questionnaire based both on farm structure parameters and on open questions concerning the general farm functioning and the specific innovations adopted by farmers. The farm innovations covered different domains: production techniques (i.e. new grassland mixtures), products (i.e. cheese processing) and farm organization (i.e. labels and marketing). Several innovations were often identified within the same farm. Most farmers’ strategies were oriented towards the reduction of production costs. Their decisions could be a good example for other potential innovators.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)